Subwavelength Racetrack Resonators With Enhanced Critically Coupled Tolerance for On-Chip Sensing - Lijun Huang (IEEE Access, 2021)
We propose a coupled-tolerant subwavelength photonic racetrack resonator (PRR) on the silicon-on-insulator (SOI) platform, in which a subwavelength grating (SWG) PRR is coupled to a symmetrical SWG bus waveguide. The material equivalent refractive index can be manipulated by the SWG characteristic and thus an additional fabrication degree of freedom can be achieved. The resonant characteristics can be improved significantly by controlling the pillar size and increasing the interaction length between SWG racetrack and bus waveguide (RBW). The simulation results show that the PRR has a high-quality factor and large extinction ratio around 1550nm. Two groups of SWG and strip waveguide (SW) PRRs are fabricated. The fabrication tolerance is tested when fabrication error is changed from 0 to 20 nm and the quality factor is more than 7000 in de-ionized water. The testing results show that the tolerance in SWG-PRR has a 2.0-fold improvement than that in the SW-PRR. Then a fabricated SWG-PRR is employed to monitor different concentration glycerol injected on the chip. An optimal quality factor of 9500 around 1550 nm and bulk sensitivity of 412± 0.5 nm/RIU are achieved. Therefore, the structure is a potential candidate for label-free sensing in medical diagnosis and environmental monitoring.